THE INFLUENCE OF SELF-CONCEPT AND INTIMATE FRIENDSHIP ON FEAR OF MISSING OUT (FOMO) IN ADOLESCENT USERS - Mawardani, Elsavira Diah; Ansyah, Eko Hardi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the influence of Self-Concept and Intimate Friendship on Fear of Missing Out (FoMO) in adolescent Instagram users in Sidoarjo. FoMO is a psychological event that is increasing along with intensive use of social media, especially among adolescents. Method: Quantitative method using a survey approach. The sample of this study amounted to 200 adolescents who were determined using purposive sampling technique or certain criteria. The instrument used in the FoMO scale was adapted from Wegmann, Oberst, Stodt & Brand. The self-concept scale from William H. Fitts and the intimate friendship scale from Etriya Miranda. The data will be analyzed by multiple linear regression using IBM SPSS software version 26. Results: The results show that self-concept has a significant positive effect on FoMO (p=0.002), meaning that the lower the self-concept tends to be the higher the individual experiences FoMO. On the other hand, intimate friendship has a significant negative effect on FoMO (p=0.000), meaning that the stronger the friendship relationship, the lower the level of FoMO experienced. The results of the analysis show that adolescents with low self-concept tend to experience social anxiety and social comparison on social media, while intimate friendship acts as a protective factor in reducing the impact of FoMO..Novelty: In this study, the novelty lies in the empirical analysis of the relationship between self-concept and intimate friendship on FoMO in adolescent Instagram users in Sidoarjo. The findings provide important insights for parents, educational practitioners and academics in understanding the psychosocial factors that can influence FoMO and designing effective interventions in reducing the adverse effects of social media use.The abstract is important because many journal readers first read the abstract to determine if the entire article is worth reading.